THE 10 NEW BALI PROJECT IN INDONESIA, REAL OR GIMMICK - Ghifary Ramadhan; Ahmad Hudaiby Galih Kusumah (UNIVERSITAS PAKUAN, 2022)
This article discusses the Ten New Bali project program launched by the former Minister of Tourism and Culture Arief Yahya during the first period of President Joko Widodo's administration, ten tourist attractions that have been selected will be formed and aligned like Bali. The Ten New Bali Project has changed its program to the Five Super Priority Destinations program, the program only focuses on five tourist destinations, namely Lake Toba, North Sumatra, Borobudur Temple, Central Java, Mandalika, West Nusa Tenggara, Labuan Bajo, East Nusa Tenggara and Likupang, North Sulawesi. This project is expected to boost the economy, human resources of the local community and tourist arrivals. The purpose of this study is to identify how far the development of the five super priority destination projects has gone. Qualitative descriptive method was used in this study by using online media news sources and literature reviews as data sources. The results show that the correlation between tourism agencies and stakeholders has a very important role in accelerating the success of the Five Super Priority Destinations program and the Five Super Priority Destinations Project has succeeded in proving one tourist destination that has been inaugurated, namely Mandalika in West Nusa Tenggara, it can be concluded that the Lima project Super Priority Destinations are already 20% running and require a lot of time.